RESPONSIBILITES OF THE NURSE IN THE URGENCY AND EMERGENCY IN THE EMERGENCY CARE UNIT - Costa Soares Silva, Talita; Thallyta Alexandre de Pontes, Arunna; de Oliveira Souza, Eclesia; Gomes do Nascimento, Evelyn; Alexandre Judeikis, Guilherme; Santos Sousa, Kallyany; Feitosa Rodrigues, Lutigard; Casado de Freitas Silva, Rosany; Kennedy Almeida Barros, Victor; de Araújo Evangelista, Wanessa; da Silva Caldas, Walissioneide (Health and Society, 2022)
This study is a bibliographic, descriptive, exploratory and qualitative research. The research took place in July and August, 2021, in the following databases: LILACS (Latin American Caribbean Literature on Health Sciences), MEDLINE (Medical Literature Analysis and Retrieval System Online) and BDENF (Bibliographic Database Specialized in the Nursing Area. The following descriptors were used: Nursing; Urgency; Emergency and Assistance, according to the Health Sciences Descriptors (DeCS) crossed by the Boolean operator “AND.” The study gathered 11 articles in its final sample. emergency care (UPA), the nurse is the foundation of the urgency and emergency service together with his team.The nursing professional has a dual-dimensional work, care and management, which are focused on the individual and the collective.